207k views
0 votes
Solve the equation 6(2x + 4)2 = (2x + 4) + 2.

User Bob Dust
by
4.2k points

2 Answers

4 votes

Intro:

Hello!!! Princess Sakura here ^^

Explanation:

First I would distribute what I can...


6(2x+4)2=(2x+4)+2\\24x+48=2x+4+2

Now we combine like terms...


24x+48=2x+6

Subtract 2x from both sides...


22x+48=6

Subtract 48 from both sides...


22x=-42

Divide both sides by 22...


x=-(21)/(11)

So the answer is
-(21)/(11)

User Alexrussell
by
5.4k points
2 votes

Answer:

-21/11

Explanation:

User ManishKungwani
by
5.0k points